2018
DOI: 10.1007/jhep10(2018)035
|View full text |Cite
|
Sign up to set email alerts
|

Many-body chaos and energy dynamics in holography

Abstract: Recent developments have indicated that in addition to out-of-time ordered correlation functions (OTOCs), quantum chaos also has a sharp manifestation in the thermal energy density two-point functions, at least for maximally chaotic systems. The manifestation, referred to as pole-skipping, concerns the analytic behaviour of energy density two-point functions around a special point ω = iλ, k = iλ/v B in the complex frequency and momentum plane. Here λ and v B are the Lyapunov exponent and butterfly velocity cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
313
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(321 citation statements)
references
References 50 publications
7
313
1
Order By: Relevance
“…Let us denote that as one expects, when ν = 0 and b = 0, equation (2.51) simplifies to what was found for the Schwarzschild case in [33]. Obviously, when ω = iω * = i2πT , all the other fields decouple from δg vv at the horizon and we are left with…”
Section: Pole-skipping Of Energy Density Green's Function From Hologrmentioning
confidence: 75%
See 2 more Smart Citations
“…Let us denote that as one expects, when ν = 0 and b = 0, equation (2.51) simplifies to what was found for the Schwarzschild case in [33]. Obviously, when ω = iω * = i2πT , all the other fields decouple from δg vv at the horizon and we are left with…”
Section: Pole-skipping Of Energy Density Green's Function From Hologrmentioning
confidence: 75%
“…Such feature may be universal among the systems which are or are close to being maximally chaotic. In [33] some further strong support for the pole-skipping phenomenon in such systems was found. By studying the linearized Einstein equations around a static black hole geometry, it was shown that the pole-skipping is universal for general systems at finite temperature, dual to Einstein gravity coupled to matter.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…To elucidate the key ideas of [17] as well as [11] that are relevant to our discussion of pole-skipping, we will first consider a minimally coupled scalar field ϕ in the uncorrected background, i.e. AdS 5 black brane 2 , ds 2 = −r 2 f (r)dv 2 + 2dvdr + r 2 (dx 2 + dy 2 + dz 2 ).…”
Section: Review Of Key Ideasmentioning
confidence: 99%
“…In [10], this pole-skipping phenomenon was also explained in terms of the shift symmetry of an effective hydrodynamic description. The pole-skipping was also analytically studied in [11] as an universal behavior near the horizon where the timetime component of the Einstein equation (in ingoing Eddington-Finkelstein coordinates) vanishes such that the dual retarded two point function is not uniquely defined. The poleskipping phenomenon has also been checked to hold for SYK system [12] and 2D CFT with large central charge [13].…”
Section: Introductionmentioning
confidence: 99%